Model Request for Proposal (RFP) Selection of Legal Advisers - Planning Commission (Planning Commission, 2009)
For addressing the present infrastructure deficit across sectors and for meeting the requirements arising out of a robust growth in GDP, a large volume of investment would be necessary for building new infrastructure projects. Public sector alone cannot meet this requirement, both in terms of funds as well as capacity. The Government has, therefore, taken several initiatives to attract private investment through Public Private Partnerships (PPP). PPP transactions involve diverse and conflicting interests of different stakeholders including the government, investors, lenders and users. An ill-conceived PPP contract can easily compromise user interests by recovery of higher charges and provision of low quality services.
Planning Commission Government of India
Planning Commission Government of India